Biohydrogen production from wastewater-based microalgae: Progresses and challenges. (30th October 2022) - Ahmed, Shams Forruque; Mofijur, M.; Nahrin, Muntasha; Chowdhury, Sidratun Nur; Nuzhat, Samiha; Alherek, May; Rafa, Nazifa; Ong, Hwai Chyuan; Nghiem, L.D.; Mahlia, T.M.I.
Abstract: Microalgae originating from wastewater has been exhibiting particularly promising results in terms of biohydrogen production and wastewater treatment. This paper aims to review the factors affecting production, pretreatment techniques to improve synthesis, advanced technologies utilized for enhancing biohydrogen production, and techno-economic feasibility evaluation of the processes at a commercial scale. Microalgae possess metabolic components to synthesize biohydrogen using photobiological and fermentative processes but must undergo pretreatment for efficient biohydrogen production. The efficiency of these processes is influenced by factors such as the microalgae species, light intensity, cell density, pH, temperature, substrates, and the type of bioreactors. Moreover, many limitations, such as oxygen sensitivity, altered thylakoid constitution, low photon conversion efficiency, light capture disruption, and the evolution of harmful by-products hinder the sustainability of biohydrogen production processes. High operational and maintenance costs serve as the major bottleneck in the scaling up of the process as an industrial technology. Therefore, future research needs to be directed towards increasing optimization of the processes by reducing energy and resource demand, recycling metabolic wastes and process components, genetically engineered microalgae to adopt more efficient routes, and conducting pilot studies for commercialization. Highlights: Wastewater-based microalgae is a potential source of biohydrogen. Factors affecting the biohydrogen production from microalgal biomass are discussed. Technologies related to biohydrogen production from microalgae are reviewed. Key challenges of biohydrogen production process from microalgae are highlighted.